Ադրբեջանի հայ բնակչության գործոնը քաղաքական օրակարգում - Մանասյան, Ալեքսանդր Ս. (ՀՀ ԳԱԱ հրատ.)
Образ возобновившегося в 1988 году этнополитического конфликта в бывшей АзССР НКАО в корне не соответствует его сути во многих отношениях. Руководствуясь принципом “не погружаться в историю”, посредники при этом исходят именно из ставших уже историей реалий 1988 г., не рассматривая, ни факта распада СССР, ни породивших конфликт событий начала XX в. Эта избирательность оставляет за бортом не только исторические, но и признанные международным сообществом правовые и политические факты, в том числе непосредственно относящиеся к конфликту действующие договора и соглашения. The image of the ethnopolitical conflict of NKAO revitalized in 1988 within the former AzSSR is radically distinct from its substance in many aspects. Guided by the principle of not meddling with history, the mediators proceeded from the very realities of 1988 that have already become history, disregarding both the decomposition of the USSR or the origin of the conflict in the early 20th century. This selective approach sweeps aside both the historical and the internationally recognized legal and political facts, including the treaties and agreements that are currently in force.
Keywords: Քաղաքականություն